A multi-method comparison of autobiographical memory impairments amongst younger and older adults. (4th May 2021) - Barry, Tom J.; Gregory, James D.; Latorre, Jose M.; Ros, Laura; Nieto, Marta; Ricarte, Jorge J.
Abstract: Objectives: Research indicates that, compared to younger adults, older adults have difficulty recalling memories of specific past events (those lasting less than 24 h) and this difficulty is associated with depression. These studies are largely confined to a single measure of specific memory recall and there are conflicting findings when alternative measures are used. This investigation provides the first comparison of memory specificity between younger and older adults using several different measures. Method: Older ( n  = 105) and younger ( n  = 88) adults completed the Autobiographical Memory Test (AMT), Autobiographical Memory Interview (AMI) and Sentence Completion for Events from the Past Test (SCEPT) and the number of specific memories was quantified for each measure. Participants also completed the Beck Depression Inventory Version II (BDI-II). Results: Compared to younger adults, older adults recalled fewer specific memories in the AMT and more specific memories in the AMI. This latter effect was particularly pronounced for memories related to childhood. There was no group difference in responses in the SCEPT. There was no evidence of an association between memory specificity and depression for any of the measures. Conclusion: Older adults have difficulty retrieving specific memories after cuing by nouns and adjectives, as in the AMT, but they have enhanced recall of specific memories after cuing by life periods, as in the AMI, and this is particularly true of memories related to childhood. Individual differences in memory specificity are not related to depression symptoms in healthy samples.